Impact of inflammatory markers on survival in patients with limited disease small-cell lung cancer undergoing chemoradiotherapy - Bernhardt, Denise; Aufderstraße, Sophie; König, Laila; Adeberg, Sebastian; Bozorgmehr, Farastuk; Christopoulos, Petros; El-Shafie, Rami; Hörner-Rieber, Juliane; Kappes, Jutta; Thomas, Michael; Herth, Felix; Steins, Martin; et al. (Cancer management and research, 2018)
Impact of inflammatory markers on survival in patients with limited disease small-cell lung cancer undergoing chemoradiotherapy Denise Bernhardt,1–3,* Sophie Aufderstrasse,1,2,* Laila König,1–3 Sebastian Adeberg,1–4 Farastuk Bozorgmehr,5,6 Petros Christopoulos,5,6 Rami A El Shafie,1,2 Juliane Hörner-Rieber,1–3 Jutta Kappes,6,7 Michael Thomas,5,6 Felix Herth,6,7 Martin Steins,5 Jürgen Debus,1–4 Stefan Rieken1–3 1Department of Radiation Oncology, University Hospital Heidelberg, Heidelberg, Germany; 2Heidelberg Institute of Radiation Oncology (HIRO), Heidelberg, Germany; 3Heidelberg Ion-Beam Therapy Center (HIT), Heidelberg, Germany; 4Clinical Cooperation Unit Radiation Oncology, German Cancer Research Center (DKFZ), Heidelberg, Germany; 5Department of Thoracic Oncology, Thoraxklinik, Heidelberg University, Translational Lung Research Centre Heidelberg (TLRC-H), Heidelberg, Germany; 6German Centre for Lung Research (DZL), Heidelberg, Germany; 7Department of Pneumology, Thoraxklinik, Heidelberg University, Heidelberg, Germany *These authors contributed equally to this work Background: Systemic inflammation appears to play a role in the progression of numerous solid tumors by promoting tumor proliferation. Our current study aimed to evaluate the role of inflammatory markers in limited disease (LD) small-cell lung cancer (SCLC) patients undergoing thoracic chemoradiotherapy (TCR). Patients and methods: We retrospectively analyzed a total number of 350 SCLC patients diagnosed with LD SCLC who received TCR between 1999 and 2017 and had available blood tests within 2 weeks prior to the start of TCR. Serum C-reactive protein (CRP), neutrophil-to-lymphocyte ratio (NLR), lactate dehydrogenase (LDH), hemoglobin (Hb) levels, and platelet count (Pc) were evaluated as potential inflammatory markers. Kaplan–Meier survival analysis was performed for overall survival (OS). For comparison of survival curves, the log-rank (Mantel–Cox) test was used. Univariate and multivariate Cox proportional HRs were used to assess the influence of cofactors on OS. Results: Univariate analysis for OS revealed a statistically significant effect for LDH >400 U/L (HR 2.05 U/L; 95% CI 1.29–3.26 U/L; P=0.002), prophylactic cranial irradiation (PCI; HR 0.58; 95% CI 0.40–0.85; P=0.005), CRP >50 mg/L (HR 1.49 mg/L; 95% CI 1.05–2.10 mg/L; P=0.026), and Karnofsky performance scale (KPS) <70% (HR 1.35%; 95% CI 1.02–1.80%; P=0.035). NLR, age (>70 years), Hb levels, and Pc did not influence survival. In multivariate analysis, OS was significantly affected by PCI (HR 0.64; 95% CI 0.43–0.94; P=0.026), LDH >400 U/L (HR 1.91 U/L; 95% CI 1.21–3.05 U/L; P=0.006), and CRP >50 mg/L (HR 1.43 mg/L; 95% CI 1.01–2.04 mg/L; P=0.045). KPS (≤70%) did not influence survival in multivariate analysis. Conclusion: Elevated CRP and LDH seem to be the independent prognostic factors for OS in LD SCLC patients undergoing TCR. However, elevated NLR was not found to be an independent prognostic factor for OS if taken prior to TCR. LDH and CRP are easily available blood tests and do not require additional resources for routine use and could be useful for clinical decision making. Keywords: small-cell lung cancer, limited disease, comorbidity, NLR, LDH, CRP